PENDAMPINGAN DETEKSI DINI TUMBUH KEMBANG ANAK DENGAN MENGGUNAKAN SDIDTK PADA GURU PAUD DAN TK DI KECAMATAN SOCAH KABUPATEN BANGKALAN - Uswatun Khasanah; Badriyah Badriyah; Sutio Rahardjo; Anis Nurlaili; Feftin Hendriyani (Community Development Journal, 2019)
The comprehensive quality guidance of child growth and development is carried out during critical periods through the activities of stimulation, detection and early intervention of child growth deviation. This activity is a comprehensive and coordinated activity held in the form of partnerships between families (parents, child caregivers and other family members), communities (cadres, community leaders, professional organizations, non-governmental organizations) and professional staff (health, education and society ).The participation of PAUD teachers as one of the indirect targets in implementing SDIDTK is expected to help improve the quality of early childhood growth and readiness to enter the level of formal education. In Socah, there are 292 pre-school children, with 35 PAUD and TK and most of the existing PAUD and TK teachers have never received knowledge or training about SDIDTK. The results showed that of PAUD?TK teachers who participated in the activity, in growth assessment and all PAUD / TK teachers were able to do it correctly. Whereas, measurement of development, at the first evaluation of activities, there were still those who could not properly carry out the development evaluation using KPSP but at the second and third evaluation all PAUD / TK teachers were able to do it correctly..